1998
DOI: 10.1152/jn.1998.79.5.2568
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor–Mediated Mechanisms Involved in the Expression of Learned Activity of Primate Striatal Neurons

Abstract: To understand the mechanisms by which basal ganglia neurons express acquired activities during and after behavioral learning, selective dopamine (DA) receptor antagonists were applied while recording the activity of striatal neurons in monkeys performing behavioral tasks. In experiment 1, a monkey was trained to associate a click sound with a drop of reward water. DA receptor antagonists were administered by micropressure using a stainless steel injection cannula (300 microm ID) through which a Teflon-coated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
55
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 49 publications
13
55
0
Order By: Relevance
“…These data further support that the sAHP after driven activity may underlie the pause responses in cholinergic interneurons (Reynolds et al, 2004;Wilson and Goldberg, 2006). Dopaminergic activity is involved in the pause response (Aosaki et al, 1994a,b;Watanabe and Kimura, 1998), presumably by potentiating excitatory synaptic inputs that increase sAHP amplitude (Reynolds et al, 2004). However, synaptic inputs can be amplified by intrinsic membrane conductances (Wilson, 2005), raising a possibility that dopaminergic modulation of these conductances may also contribute to the pause response.…”
Section: Dopaminergic Potentiation Of Depolarization-induced Suppresssupporting
confidence: 56%
See 1 more Smart Citation
“…These data further support that the sAHP after driven activity may underlie the pause responses in cholinergic interneurons (Reynolds et al, 2004;Wilson and Goldberg, 2006). Dopaminergic activity is involved in the pause response (Aosaki et al, 1994a,b;Watanabe and Kimura, 1998), presumably by potentiating excitatory synaptic inputs that increase sAHP amplitude (Reynolds et al, 2004). However, synaptic inputs can be amplified by intrinsic membrane conductances (Wilson, 2005), raising a possibility that dopaminergic modulation of these conductances may also contribute to the pause response.…”
Section: Dopaminergic Potentiation Of Depolarization-induced Suppresssupporting
confidence: 56%
“…Recordings of cholinergic interneurons in vivo (Wilson et al, 1990;Reynolds et al, 2004) and in vitro (Jiang and North, 1991;Bennett and Wilson, 1999;Goldberg and Wilson, 2005;Wilson, 2005) have revealed that these cells correspond to the tonically active neurons (TANs) in the striatum. The TANs exhibit pauses in tonic firing in response to salient stimuli during associative learning (Aosaki et al, 1994a,b;Apicella, 2002;Morris et al, 2004), which are dependent on dopaminergic inputs from the substantia nigra (Aosaki et al, 1994a;Watanabe and Kimura, 1998). However, the cellular mechanisms underlying the pause response are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to motivational aspects of PR performance, studies show that nigro-striatal dopaminergic projections (Ljungberg et al 1991;Schultz et al 1993a;Schultz et al 1993b) and D 2 -expressing cholinergic interneurons (Watanabe and Kimura 1998) may encode motivation and reward value in a plastic manner. In particular Watanabe and colleagues show that learned, reward-associated alterations in striatal neuron discharge rates are attenuated by local application of both D 1 -like and D 2 -like antagonists (Watanabe and Kimura 1998). Thus, it is likely that both the D 1 -like and D 2 -like antagonist effects on PR performance are likely to be specific for motivational aspects of the task.…”
Section: Discussionmentioning
confidence: 99%
“…The drug solution was pressure-injected, 0.2 l every 30 s for 10 times, for a total of 2 l. We used ((R)-(ϩ)-7-chloro-8-hydroxy-3-methyl-1-phenyl-2,3,4,5-tetrahydro-1H-3-benzazepine) (SCH23390; 8 g/l) as a dopamine D 1 antagonist and Eticlopride hydrochloride (6 g/l) as a dopamine D 2 antagonist (Sigma, St. Louis, MO), both directly dissolved by saline. These doses were chosen based on the previous reports (Watanabe and Kimura, 1998;Bari and Pierce, 2005). We also injected saline as a separate experiment to ensure the effect was not caused by any mechanical effect by liquid injection (data are in supplemental material, available at www.jneurosci.org).…”
Section: Methodsmentioning
confidence: 99%